PSYCHOLOGICAL-SPIRITUAL APPROACH OF CAREGIVERS IN DRUG REHABILITATION AT SABILUL HIKMAH POLOWIJEN ISLAMIC BOARDING SCHOOL - Ulfiandi, Ihsan Zikri; Wahyuni, Esa Nur (Proceeding of International Conference of Islamic Education, 2024)
The drug problem in Indonesia is complex. In the past decade, this problem has become rife. It is proven that the number of drug abusers or addicts is significant, along with the increasing disclosure of drug crime cases that are increasingly diverse in patterns and the more massive the syndicate network. There is a need for prevention and recovery of victims, one of which is by rehabilitation carried out in Islamic boarding schools. The focus to be researched is: 1) the concept of caregiver leadership 2) psycho-spiritual approach in rehabilitation, 3) the impact experienced after rehabilitation. The research uses a qualitative approach with a case study type. The research process is carried out by observing phenomena in the object of research to obtain data by looking for data on informants and documents. Research Results 1) The concept of kiai leadership is collective-collegial, consultative and instructive that rests on the authority and influence of kiai. 2) The rehabilitation process uses psychological and spiritual approaches which include the cultivation of scheduled spiritual / religious values from waking up to sleeping again (congregational prayers, istighosah, recitation, ngaji Kitab and sholawatan). Psychological approach, counseling, mentoring (observation to students starting from the initial assessment of entry, monitoring and follow-up). Then the home visit program is a home visit whose purpose is to strengthen parents or relatives Discussion. 3) Changes in behavior / attitude towards students, This can be seen from the emotional attitude of students who slowly change and also the habits of students who become diligent in worship and cause students' religiosity. Increasing the skills possessed by students, and increasing the social community of students with the surrounding environment.